Design of Indoor Lighting Circuit with Automatic Brightness Adjustment is Analyzed. Issue 1 (February 2020) - Zhai, Dong; Li, HongWei
Abstract: With the continuous progress of science and technology, People's Daily life is also toward the direction of intelligent development, intelligent technology embodies in every aspect of people's lives. As an important part of people's life and production, indoor lighting also gradually reflects the intelligent factors. Indoor lighting has gradually realized automatic brightness adjustment, that is, with the help of natural light brightness changes to adjust the brightness of indoor lighting. The purpose of this paper is to realize the automatic adjustment of indoor lighting through the design of indoor lighting circuit for automatic brightness adjustment. This article first to automatically adjust the brightness has carried on the summary of the basic circuit, secondly from circuit control principle, material selection and use of all aspects, such as the design of main circuit to automatically adjust the indoor light circuit design are discussed in detail, finally by means of indoor lighting brightness calculation method to automatically adjust the brightness of the reliability of the circuit design for testing. The experiments in this paper show that the design of indoor lighting circuit with automatic brightness adjustment is reliable and can realize the automatic adjustment of indoor lighting according to the ambient light.